Food composite leavening agent

By using a composite leavening agent with a multi-layered microcapsule structure and surface-modified nanomaterials, the problems of uneven dispersion of gas-producing components and poor storage stability in existing technologies have been solved. This achieves synchronization between the gas production rate and dough expansion, forming a uniform and fine pore structure, improving the specific volume and taste of bread, and reducing alkaline residual odor.

CN121369666APending Publication Date: 2026-01-23CARLOS (FUJIAN) FOOD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511612290.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing chemical leavening agents are prone to pre-reaction during storage, resulting in uneven dispersion of gas-producing components and loss of effective ingredients. They cannot meet the stage-specific expansion requirements of dough, leading to low specific volume and uneven pore structure in the finished product. Furthermore, the temperature response control precision of conventional embedding processes is insufficient, resulting in the collapse and coarse texture of baked products.

Method used

This composite leavening agent, employing a multi-layered microcapsule structure and surface-modified nanomaterials, utilizes gradient encapsulation technology to achieve phased release of gas-producing substances. Combined with ultrasonic-assisted mixing and a three-stage mixing process, it ensures that each component is molecularly dispersed in the matrix, forming a stable nano-starch composite network. This constructs a dual barrier, precisely matching the dough's expansion requirements.

Benefits of technology

It achieves synchronization between gas production rate and dough expansion, forming a uniform and fine pore structure, increasing bread specific volume by 30%, reducing core hardness, improving taste, inhibiting pre-reaction, eliminating alkaline residual odor, and improving storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121369666A_ABST
    Figure CN121369666A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of leavening agents, and discloses a food composite leavening agent, which comprises the following components by mass: 25-30 parts of ammonium bicarbonate; 15 to 23 parts of microencapsulated ammonium citrate; 8 to 16 parts of sodium pyrophosphate; 5 to 9.5 parts of L-potassium hydrogen tartrate; 13 to 17 parts of trehalose; 0.5 to 1.3 parts of surface modified nano silicon dioxide; and 10 to 17 parts of hydroxypropylated cassava starch. The microencapsulated ammonium citrate is formed by coating beta-cyclodextrin, and the thickness of an embedding layer is 16-20 [mu] m. The multi-layer microcapsule structure is constructed by carrying out gradient embedding on ammonium citrate through beta-cyclodextrin, so that staged release of gas production substances is realized. According to the structure, different temperature intervals are accurately matched in the baking process, it is guaranteed that the gas production rate is synchronous with the dough expansion requirement, and the problem of excessive expansion or insufficient gas production caused by concentrated release in the traditional technology is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of leavening agents, and in particular to a food compound leavening agent. Background Technology

[0002] Currently, traditional chemical leavening agents generally use physical mixing methods, which can lead to pre-reactions of gas-producing components during storage, resulting in the loss of effective ingredients. Existing encapsulation technologies mostly use a single wall material for overall coating, resulting in the concentrated release of gas-producing substances during baking, which is difficult to match the staged expansion requirements of the dough.

[0003] When the temperature reaches 60℃, acidic substances react prematurely with carbonates, and the peak gas production occurs before the gluten network is fully formed, resulting in a gas escape rate as high as 35% to 40%. In subsequent high-temperature stages, because a large amount of the effective components have been consumed, it is impossible to continuously generate gas to support pore expansion, ultimately leading to a lower specific volume and uneven pore structure in the finished product. Furthermore, conventional embedding processes lack sufficient precision in controlling the temperature response, and the mismatch between the wall material decomposition temperature and the dough expansion stage causes a discrepancy between the gas production rate and gluten strength development. This is the root cause of technical problems such as product collapse and coarse texture in baked goods. Summary of the Invention

[0004] The purpose of this invention is to provide a food compound leavening agent that solves the problems of single gas production stage, uneven component dispersion, poor storage stability, and flavor deterioration caused by by-product residues in the prior art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a food compound leavening agent, comprising the following mass fractions: Ammonium bicarbonate: 25-30 parts; Microencapsulated ammonium citrate: 15-23 parts; Sodium pyrophosphate: 8–16 parts; L-potassium hydrogen tartrate: 5–9.5 parts; Trehalose: 13-17 parts; Surface-modified nano-silica: 0.5–1.3 parts; Hydroxypropyl cassava starch: 10-17 parts.

[0006] Preferably, the microencapsulated ammonium citrate is formed by encapsulation with β-cyclodextrin, and the encapsulation layer thickness is 16-20 μm.

[0007] Preferably, the molar ratio of β-cyclodextrin to ammonium citrate is 2.1-2.3:1, and the D50 particle size of the microcapsule particles is 30-34 μm.

[0008] Preferably, the surface-modified nano-silica is a polyvinylpyrrolidone graft-modified product with a grafting rate of 23% to 27% and a particle size of 50-80 nm.

[0009] Preferably, the hydroxypropylated cassava starch has a degree of substitution of 0.08-0.12 and a moisture content of ≤8.5%.

[0010] The leavening agent system comprises seven key components, including ammonium bicarbonate and microencapsulated ammonium citrate. The microencapsulated ammonium citrate utilizes a β-cyclodextrin encapsulation structure, with the encapsulation layer thickness controlled within the range of 16-20 μm. This design achieves physical barrier against acidic components through the molecular cavity structure of β-cyclodextrin, maintaining chemical inertness at room temperature while allowing controlled release through capillary melting upon heating. The surface-modified nano-silica is a polyvinylpyrrolidone graft-modified product, with a grafting rate of 23%–27% ensuring the formation of a stable steric hindrance layer on the particle surface, effectively preventing moisture absorption and clumping. The degree of substitution of hydroxypropylated cassava starch is selected within the range of 0.08–0.12, balancing the starch's water-holding capacity and dispersibility, providing suitable moisture migration channels for the leavening reaction.

[0011] A method for preparing a food compound leavening agent includes the following steps: Step 1: Preparation of microencapsulated ammonium citrate; Step 2: Preparation of modified nano-silica; Step 3: Mix the modified nano-silica, microencapsulated ammonium citrate, and the remaining raw materials; Step 4: Sieve.

[0012] Preferably, step one specifically includes: First, prepare a 15-18 wt% aqueous solution of β-cyclodextrin and heat it to 58-62℃; Then add ammonium citrate crystals at a solid-liquid ratio of 1:3.8-4.2 to maintain the pH of the solution at 6.8-7.2; β-cyclodextrin was added in three separate additions, each 9-11 minutes apart, with the total molar ratio of β-cyclodextrin to ammonium citrate being 2.1-2.3:1. After mixing, spray drying is performed, specifically including: Inlet air temperature: 179-185℃; outlet air temperature: 76-80℃. Atomizing disc rotation speed: 19000-21000 rpm; Feed rate: 8-12 mL / min.

[0013] Preferably, step two specifically includes: The polyvinylpyrrolidone solution is an ethanol solution with a concentration of 7.5-8.5 wt% and an ethanol purity of ≥99.7%. Nano-silica and polyvinylpyrrolidone solution are placed in a ball mill for grinding; the mass ratio of nano-silica to polyvinylpyrrolidone solution is 1:4.8-5.2, the ball milling media are zirconia balls with a diameter of 0.28-0.32 mm, and the ball-to-material ratio is 8:1-10:1. After ball milling, the material undergoes a drying process. The drying conditions include: vacuum degree of -0.095 to -0.085 MPa, drying temperature of 48-52℃, and moisture content of the dried material of ≤0.6%.

[0014] Preferably, step three specifically includes: Initial mixing: Mix ammonium bicarbonate and hydroxypropylated cassava starch at 30-60 rpm for 7-11 min; Medium mixing: Add microencapsulated ammonium citrate + sodium pyrophosphate + potassium hydrogen tartrate, and mix for 10-20 min at a speed of 13-17 rpm and a vacuum of -0.065 to -0.095 MPa; Final mixing: After adding trehalose and surface-modified nano-silica, ultrasonic mixing is performed with an ultrasonic frequency of 27-29 kHz, a power density of 0.8-1.2 W / cm3, and a processing time of 4-9 min. Furthermore, the initial mixing, intermediate mixing, and final mixing are all carried out within a temperature range of 25-35℃.

[0015] Preferably, after the final mixing is completed, the material is sieved. The sieve aperture is 75-85 mesh, the amplitude is 2.3-3.2 mm, and the sieving time is 8-12 minutes.

[0016] The preparation method comprises four key steps, with microencapsulation employing a gradient encapsulation technique. After the β-cyclodextrin solution is heated to 58-62℃, the encapsulating agent is added in stages. This temperature range keeps the cyclodextrin molecules in a partially open-ring state, which is conducive to the formation of a dense coating layer. During the spray drying stage, the atomizing disc speed is controlled at 19000-21000 rpm, allowing the droplets to complete directional crystallization during flight, forming regular spherical particles with a diameter of 30-34 μm. Nano-silica modification is performed using specific ball milling parameters (zirconia ball diameter 0.28-0.32 mm), which, through mechanochemical action, promotes the covalent grafting of PVP molecular chains with the hydroxyl groups on the particle surface.

[0017] The mixing process is implemented in three stages: the initial mixing stage achieves pre-dispersion of the alkaline components and the carrier at 30-60 rpm; the intermediate mixing stage introduces a vacuum environment (-0.095 to -0.085 MPa) to inhibit the pre-reaction; and the final mixing stage combines an ultrasonic field (27-29 kHz) to break up particle agglomeration and promote the formation of a uniform coating of trehalose. The sieving process uses a 75-85 mesh sieve to effectively separate incompletely dispersed agglomerates under an amplitude of 2.3-3.2 mm.

[0018] In summary, the present invention has at least one of the following beneficial technical effects: 1. A multi-layered microcapsule structure constructed through gradient encapsulation enables the phased release of gas-producing substances. This structure precisely matches different temperature ranges during baking, ensuring that the gas production rate is synchronized with the dough's expansion requirements, avoiding the problems of over-expansion or insufficient gas production caused by concentrated release in traditional processes.

[0019] 2. By employing ultrasonic-assisted three-stage mixing combined with surface-modified nanomaterials, particle agglomeration is effectively broken up, forming a stable nano-starch composite network that ensures molecular-level dispersion of each component within the matrix.

[0020] 3. A dual barrier is constructed through the synergistic effect of the microcapsule wall material and the moisture-proof components. The dynamic hydration layer inhibits moisture penetration, and the composite wall material delays the migration of the core material, enabling the product to maintain excellent activity even in high-temperature and high-humidity environments.

[0021] 4. A phased gas-generating mechanism creates a uniform and fine porous structure, while nanoparticles enhance the mechanical strength of the gluten network. This results in a 30% increase in bread volume while reducing core hardness for a better texture.

[0022] 5. Precise encapsulation process inhibits pre-reaction, and surface modification technology reduces free ammonia generation. The product's pH value change is controlled within 0.3, effectively eliminating the alkaline residual odor of traditional leavening agents. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the method flow of the present invention. Detailed Implementation

[0024] The following is in conjunction with the appendix Figure 1 The present invention will be further described in detail below.

[0025] Example 1 Component proportions (by weight): Ammonium bicarbonate 28 parts, microencapsulated ammonium citrate 19 parts, sodium pyrophosphate 12 parts, potassium hydrogen tartrate 7.5 parts, trehalose 15 parts, surface-modified nano silica 0.9 parts, hydroxypropylated tapioca starch 13.5 parts.

[0026] Preparation steps: Preparation of microencapsulated ammonium citrate: a. Prepare a 16 wt% aqueous solution of β-cyclodextrin and heat it in a water bath to 60 ± 1 °C. b. Add ammonium citrate crystals at a solid-liquid ratio of 1:4.0, and continue stirring to maintain pH 7.0±0.1; c. Add β-cyclodextrin solution in three separate additions, each 10 minutes apart, with a total molar ratio of β-cyclodextrin:ammonium citrate = 2.2:1; d. Spray drying parameters: Inlet air temperature: 182℃; outlet air temperature: 78℃; atomizing disc rotation speed: 20000rpm; feed rate: 10mL / min; Preparation of surface-modified nano-silica: a. Prepare an 8.0 wt% polyvinylpyrrolidone ethanol solution (ethanol purity 99.8%); b. Add materials according to the mass ratio of nano-silica to solution = 1:5.0; c. Ball milling parameters: Zirconia ball diameter 0.30 mm; ball-to-material ratio 9:1; processing time 3.0 h; d. Vacuum drying: temperature 50℃; vacuum degree -0.090MPa; drying time 2.8h; final moisture content 0.5%; Mixing process: a. Initial mixing: 45 rpm; 9 min; Materials: ammonium bicarbonate + hydroxypropylated tapioca starch; b. Intermediate mixing: 15 rpm; vacuum -0.080 MPa; time 15 min; new materials: microencapsulated ammonium citrate + sodium pyrophosphate + potassium hydrogen tartrate; c. Final mixing: Ultrasonic frequency 28kHz; power density 1.0W / cm³ 3 Processing time: 6 min; New materials: Trehalose + surface-modified nano-silica; Sieving: 80 mesh screen; amplitude 2.8 mm; sieving time 10 min.

[0027] Example 2 Component proportions (by weight): Ammonium bicarbonate 25 parts, microencapsulated ammonium citrate 15 parts, sodium pyrophosphate 16 parts, potassium hydrogen tartrate 5 parts, trehalose 17 parts, surface-modified nano silica 0.5 parts, hydroxypropylated tapioca starch 17 parts.

[0028] Preparation steps: Preparation of microencapsulated ammonium citrate: a. β-cyclodextrin solution concentration 15wt%, heated to 58℃; b. Solid-liquid ratio 1:3.8, maintain pH 6.8; c. Add β-cyclodextrin at a total molar ratio of 2.1:1, at 9-minute intervals; d. Spray drying: inlet air 179℃ / outlet air 76℃, atomizing disc 19000rpm, feed 8mL / min; Preparation of surface-modified nano-silica: a. PVP ethanol solution concentration 7.5 wt% (ethanol purity 99.7%); b. Feed ratio 1:4.8; c. Ball diameter 0.28mm, ball-to-material ratio 8:1, treatment time 3.5h; d. Drying conditions: 48℃ / -0.095MPa, time 3.0h, final moisture content 0.6%; Mixing process: a. Initial mixing: Mix at 30 rpm for 11 min; Materials: Ammonium bicarbonate + hydroxypropylated tapioca starch; b. Medium mixing: Mix at 13 rpm under vacuum at -0.095 MPa for 20 min; New materials: Microencapsulated ammonium citrate + sodium pyrophosphate + potassium hydrogen tartrate; c. Final mixing: Ultrasonic 27kHz / 0.8W / cm 3 Processing time: 9 min; New material added: trehalose + surface-modified nano silica; Sieving: 75 mesh sieve; Amplitude: 3.2 mm; Sieving time: 12 min.

[0029] Example 3 Component proportions (by weight): Ammonium bicarbonate 30 parts, microencapsulated ammonium citrate 23 parts, sodium pyrophosphate 8 parts, potassium hydrogen tartrate 9.5 parts, trehalose 13 parts, surface-modified nano silica 1.3 parts, and hydroxypropylated tapioca starch 10 parts.

[0030] Preparation steps: Preparation of microencapsulated ammonium citrate: a. 18 wt% β-cyclodextrin solution, heated to 62 °C; b. Solid-liquid ratio 1:4.2, maintain pH 7.2; c. Add β-cyclodextrin at a total molar ratio of 2.3:1, at 11-minute intervals; d. Spray drying: inlet air 185℃ / outlet air 80℃, atomizing disc 21000rpm, feed 12mL / min; Preparation of surface-modified nano-silica: a. 8.5 wt% PVP ethanol solution (ethanol purity 99.9%); b. Feed ratio 1:5.2; c. Ball diameter 0.32mm, ball-to-material ratio 10:1, treatment time 2.5h; d. Drying conditions: 52℃ / -0.085MPa, time 2.5h, final moisture content 0.4%; Mixing process: a. Initial mixing: Mix at 60 rpm for 7 min; Materials: Ammonium bicarbonate + hydroxypropylated tapioca starch; b. Medium mixing: Mix at 17 rpm under vacuum at -0.065 MPa for 10 min; New materials: Microencapsulated ammonium citrate + sodium pyrophosphate + potassium hydrogen tartrate; c. Final mixing: Ultrasonic waves 29kHz / 1.2W / cm² 3 Processing time: 4 min; New materials: trehalose + surface-modified nano silica; Sieving: 85 mesh sieve; Amplitude: 2.3 mm; Sieving time: 8 min.

[0031] Comparative Example 1 The difference compared to Example 1 is as follows: No surface-modified nano-silica was used; Hydroxypropylated cassava starch was replaced with unmodified cassava starch; The remaining components and processes are the same.

[0032] Comparative Example 2 The difference compared to Example 1 is as follows: All β-cyclodextrin is added at once during the microencapsulation process; The rotation speed of the spray drying atomizing disc was changed to 15000 rpm; The remaining components and processes are the same.

[0033] Comparative Example 3 The difference compared to Example 2 is as follows: Replace the polyvinylpyrrolidone solution with an equal volume of pure ethanol; The ball milling process was cancelled and replaced with magnetic stirring; The remaining components and processes are the same.

[0034] Comparative Example 4 The difference compared to Example 1 is as follows: In the final mixing stage, conventional stirring (60 rpm) is used instead of ultrasonic treatment; The intermediate mixing stage is carried out under normal pressure; The remaining components and processes are the same.

[0035] Comparative Example 5 The difference compared to Example 3 is as follows: Microencapsulated ammonium citrate was replaced with physical mixing (without encapsulation); Nano-silica is used directly without modification; The remaining components and processes are the same.

[0036] Comparative Example 6 The difference compared to Example 1 is as follows: The molar ratio of β-cyclodextrin to ammonium citrate was 1.9:1; The unmixed ultrasonic frequency is 25kHz. 100 mesh screen; The remaining components and processes are the same.

[0037] Experiment 1 Experimental objective: To verify the effect of microencapsulation on the control of gas production process and to evaluate the differences in gas production characteristics among different implementation schemes.

[0038] Test sample Examples 1-3, Comparative Example 1 (surface-modified nano-silica / unmodified starch), Comparative Example 2 (non-embedded), Comparative Example 5 (unembedded ammonium citrate).

[0039] Experimental equipment TA-Q2000 thermogravimetric analyzer (TA Instruments, USA); Customized gas collection system (accuracy ±0.1 mL); Julabo-FP50 thermostatic circulator; Experimental steps Sample pretreatment Grind each leavening agent sample through a 100-mesh sieve; Accurately weigh 1.000±0.002g of the sample to be tested; Gas production measurement; a. Place the sample in a gas collection reactor; b. Increase the temperature from 30°C to 120°C at a rate of 5°C / min; c. Record CO2 release in real time (data collected every 0.5°C); Data collection points Initial gas production temperature T0 (CO2 release rate ≥ 0.1 mL / min·g); Gas production at 50℃: Q1; Gas production at 80℃: Q2; Gas production at 110℃: Q3; Total gas production Qtotal = Q1 + Q2 + Q3; Gas production rate calculation V = ΔQ / Δt (average speed in the 30-50℃ range); Experimental conditions Relative humidity control: 45±5%RH; Carrier gas flow rate: Nitrogen 20 mL / min; Number of repeated tests: n = 5; The test data is shown in Table 1: Table 1: Experiment Summary Microencapsulation significantly improved the temperature response characteristics of the gas generation process. Experimental data showed that the β-cyclodextrin-coated sample exhibited a gas generation peak near 80℃, which is closely related to the glass transition temperature of the capsule wall material. When the ambient temperature reached the melting point of the wall material, the microcapsules formed directional channels to release acidic substances, promoting the staged decomposition of ammonium bicarbonate. The gradient encapsulation process, by controlling the addition rhythm of β-cyclodextrin, resulted in the formation of a multi-layered, dense structure in the capsule wall, effectively delaying the premature release of the core material.

[0040] The synergistic effect of surface-modified nano-silica and hydroxypropyl starch constructed a stable gas diffusion channel. Compared with the unmodified Comparative Example 1, the Example group maintained a continuous gas production of 24.1–31.5 mL / g in the high-temperature zone (110°C), which is attributed to the anchoring effect of nanoparticles in the starch network. The PVP graft layer adsorbs water molecules through hydrogen bonding, forming a local humidity buffer layer to ensure that the reaction system retains sufficient activity in the later stages of baking.

[0041] The optimization of parameters in the three-stage mixing process, particularly the application of ultrasonic treatment, enabled the components to achieve molecular-level dispersion. Although Example 3 used high-content microcapsules (23 parts), its gas production rate curve maintained a smooth transition, attributed to the ultrasonic cavitation effect breaking down particle agglomerates. Vacuum mixing conditions suppressed the occurrence of pre-reactions, resulting in a 54%–57% increase in total gas production compared to the comparative example, without the generation of free ammonia odor, thus confirming the rationality of the process parameter design.

[0042] Experiment 2 Experimental Objective To verify the synergistic moisture-proof effect of surface-modified nano-silica and starch carrier, and to evaluate the storage stability of different implementation schemes.

[0043] Test sample Examples 1-3, Comparative Example 1 (without nano silica / unmodified starch), Comparative Example 3 (without grafted PVP), Comparative Example 6 (out of range parameters).

[0044] Experimental equipment Binder-KBF720 constant temperature and humidity chamber; FT4 powder rheometer (Freeman, UK); Malvern-Zetasizer-Nano-ZSP Potential Analyzer; Experimental steps Accelerated moisture absorption test a. Spread the sample evenly on the petri dish (2mm thick); b. Place in an environment of 38℃ / 85%RH for 7 consecutive days; c. Weigh and record changes in moisture content daily at set times; Agglomeration rate determination a. Take samples on day 3 / 7 and pass them through a 250μm sieve; b. Calculate the clumping rate = (1 - pass rate) × 100%; Surface property analysis a. Surface charge was measured using a Zeta potentiometer; b. Infrared spectroscopy analysis of changes in the intensity of the hydroxyl absorption peak; Liquidity test a. Angle of repose and compressibility were determined using FT4. b. Calculate the flow function fffc value; Experimental conditions Initial moisture content of the sample: 5.2%–5.8%; Number of test repetitions: n = 3; The test data is shown in Table 2: Table 2: Experiment Summary Polyvinylpyrrolidone (PVP) grafted onto nano-silica significantly improves the moisture-proof performance of the system by forming a steric hindrance layer. Experimental data show that the absolute value of the Zeta potential of the surface-modified sample reaches -29.8 to -41.2 mV, which is more than twice that of the unmodified sample. This is due to the chemical bonding between the amide groups on the PVP molecular chain and the hydroxyl groups on the particle surface, which effectively reduces the surface energy. The optimized design with a grafting rate of 23% to 27% constructs a suitable organic coating layer on the surface of the nanoparticles, which not only blocks the adsorption of water molecules but also maintains an appropriate spacing between particles.

[0045] The degree of substitution of hydroxypropylated cassava starch has a synergistic effect on enhancing its moisture-proof performance. When the degree of substitution is in the range of 0.08-0.12, the hydroxyl groups in the starch molecules are replaced by hydroxypropyl groups, reducing the density of hydrophilic groups. Simultaneously, the three-dimensional network structure formed by the modified starch and trehalose fixes free water molecules through hydrogen bonding, resulting in a final moisture content of 7.1%–8.3% in the example group, significantly lower than that of the comparative example. This composite carrier structure also forms physical isolation between particles, inhibiting agglomeration caused by capillary effects.

[0046] The ball milling conditions in the process parameters directly affect the stability of the moisture-proof performance. The combination of zirconia ball diameter (0.28–0.32 mm) and ball-to-material ratio (8:1–10:1) ensures the uniformity of the mechanochemical modification. Comparative Example 3, with samples treated with magnetic stirring, showed an agglomeration rate of 37.2%, confirming the crucial role of ball milling in ensuring the uniformity of PVP grafting. Vacuum drying conditions (-0.095–-0.085 MPa) promote rapid removal of solvent molecules, preventing secondary agglomeration during drying, which is consistent with the excellent flowability test results (angle of repose < 36°) of the example group.

[0047] Experiment 3 Experimental Objective The effect of ultrasonic mixing process on the dispersion of nanoparticles was verified, and the component distribution uniformity of different implementation schemes was evaluated.

[0048] Test sample Examples 1-3, Comparative Example 4 (conventional stirring), Comparative Example 5 (unencapsulated / unmodified); Experimental equipment Malvern-Mastersizer-3000 laser particle size analyzer; Hitachi-SU8010 field emission scanning electron microscope; Thermo-Scientific-DXR2 micro Raman spectrometer; Experimental steps Particle size distribution test a. Disperse 0.5g of the sample in 50mL of anhydrous ethanol; b. Test immediately after ultrasonic dispersion for 2 minutes; c. Record D10 / D50 / D90 and Span value (Span = (D90-D10) / D50); Micromorphological analysis a. SEM observation of the sample after gold sputtering (5kV, 10kx); b. Count the number of nano-silica aggregates (count aggregates >200nm per field of view); Raman surface scanning a. Select a 50×50μm region for chemical imaging; b. Analyze the characteristic peak of trehalose (1120 cm⁻¹). -1 Distribution uniformity; c. Calculate the relative standard deviation (RSD) value; Experimental conditions Ambient temperature: 25±1℃; Relative humidity: 40±5%; Number of test repetitions: n = 5; The test data is shown in Table 3: Table 3: Experiment Summary The cavitation effect generated by ultrasonic treatment significantly improved the dispersion state of nanoparticles. High-frequency vibration formed microjets in the liquid phase, effectively breaking up soft agglomerates of nano-silica. Experimental data showed that the number of agglomerates in the example group was only 23%–29% of that in the comparative example. The surface-modified nanoparticles formed a stable dispersion system in the starch matrix through the steric hindrance of the PVP long chains, and the Span value decreased to 1.6–2.1, demonstrating an improvement in particle size distribution concentration.

[0049] The application of vacuum conditions in the three-stage mixing process reduced the interference of air bubbles on the dispersion process. SEM images showed that the trehalose in the example group was continuously coated in a film with an RSD value of less than 16%, indicating that the sugar formed a uniform coating on the particle surface. This structure effectively isolates acidic substances from premature contact with sodium bicarbonate. In contrast, Comparative Example 5, due to the lack of encapsulation treatment, resulted in localized pH abnormalities, leading to component aggregation.

[0050] The energy input control in the final mixing stage directly affects the final dispersion quality. Example 3 uses a higher ultrasonic power (1.2 W / cm²). 3 However, shortening the processing time, while avoiding overheating that could damage the capsule wall, allows the nanoparticles to achieve a monodisperse state. Conventional stirring in Comparative Example 4 failed to provide sufficient shear force, increasing the D90 value by 65%, confirming the necessity of the special mixing process.

[0051] Experiment 4: Baking Application Test Experiment Description Experimental Objective To verify the performance of leavening agents in actual baking and to evaluate the impact of different implementation schemes on the quality of the finished product.

[0052] Test sample Example 1, Comparative Example 2 (Non-gradient embedding), Comparative Example 4 (Conventional mixing), Comparative Example 6 (Out-of-range parameters) Experimental equipment Brabender-Farinograph-E dough rheometer; Sanmai SM-520E proofing box; TA.XTPlus texture analyzer; Experimental steps Dough preparation a. Prepare the basic dough according to GB / T-20981-2021: 1000g of high-gluten flour; 580g of water; 12g of yeast; 15g of test sample; b. Knead the dough until it reaches the fully developed stage (dough temperature 26±1℃); Awakening monitoring a. Divide the dough into 150g portions and place them in a proofing box (38℃ / 85%RH); b. Record volume changes every 10 minutes for 90 minutes; Baking process a. Bake at 210℃ (top heat) / 190℃ (bottom heat) for 25 minutes; b. Measure the specific volume after cooling for 1 hour; Quality Analysis a. Determine the hardness of bread crumbs using a texture analyzer (probe P / 36R); b. Observe the uniformity of stomatal structure by sectioning (0-5 grade rating); Experimental conditions Baking repetitions: n = 5; The test data is shown in Table 4: Table 4: sample Maximum expansion rate (%) Specific volume (mL / g) Hardness (N) Stoma score Example 1 312.4 4.8 18.7 4.3 Comparative Example 2 278.5 4.1 24.9 3.5 Comparative Example 4 265.3 3.7 29.4 2.8 Comparative Example 6 291.2 4.3 21.5 3.9 The gradient encapsulation structure enables the phased release of gas-producing substances, dynamically matching the dough fermentation process. In Example 1, approximately 35% of the acidic substances are released during the proofing stage (38°C), prompting yeast to produce gas and form the basic gas cell structure; during the baking stage (>80°C), the microcapsules completely rupture, releasing the remaining acidic components, allowing sodium bicarbonate to fully decompose and generate supporting gas. This controlled-release mechanism results in a maximum expansion rate of 312.4%, an improvement of 12%–18% compared to the control group.

[0053] The synergistic effect of nanoparticles and starch matrix improved the gluten network strength. Scanning electron microscopy showed that the gluten protein in the example group formed a continuous three-dimensional network, and the nano-silica enhanced the network elasticity through physical cross-linking, increasing the specific volume of the finished product to 4.8 mL / g. Comparative Example 4 showed defects in the gluten structure due to uneven dispersion, with a 58% increase in hardness, confirming the key role of uniform dispersion in improving texture.

[0054] Optimized process parameters ensured complete reaction. Example 1 shows that vacuum mixing effectively suppressed pre-reaction, improving the storage stability of acidic substances. Although Comparative Example 6 used parameters close to the critical value, insufficient ultrasonic frequency led to incomplete local reactions, demonstrating the necessity of limiting the parameter range.

[0055] Experiment 5 Experimental Objective To verify the effect of microencapsulation on improving the storage stability of leavening agents and to evaluate the long-term preservation performance of different implementation schemes.

[0056] Test sample Examples 1-3, Comparative Example 1 (without nano silica / unmodified starch), Comparative Example 3 (without grafted PVP), Comparative Example 5 (without encapsulated ammonium citrate).

[0057] Experimental equipment Constant temperature and humidity test chamber (ESPECPL-3KPH); Agilent-1260-Infinity-II-HPLC system; Metrohm-859-Titrotherm ammonia nitrogen analyzer; Experimental steps Accelerated aging test a. The sample is sealed in an aluminum-plastic bag (oxygen permeability < 0.5 cc / m³). 2 ·day); b. Store at 40℃ / 75%RH for 30 days; c. Samples are taken and tested every 10 days; Analysis of active ingredients a. Determination of ammonium bicarbonate retention rate by HPLC (column: Agilent-ZORBAX-SB-Aq); b. Determination of ammonium citrate release rate by ion chromatography; By-product detection a. Determination of free ammonia content using the Kjeldahl method; b. pH value determination (1% aqueous solution); Physical property testing a. Specific surface area analysis (BET method); b. Measurement of moisture absorption weight gain rate; Experimental conditions Initial active ingredient content: ammonium bicarbonate 62.3±0.5%, ammonium citrate 22.8±0.3%; Number of test repetitions: n = 3; The test data is shown in Table 5: Table 5: Experiment Summary The dense encapsulation structure of the microcapsules effectively blocks the penetration of environmental moisture. The composite wall material formed by β-cyclodextrin and trehalose, reinforced with nano-silica, has a 38%–45% lower specific surface area compared to the comparative example, creating a low-permeability barrier. Experimental data show that the moisture absorption rate of the example group was only 2.1%–3.5%, while the unmodified comparative example 1 had a moisture absorption rate of 7.9%, confirming that surface modification significantly improves moisture-proof performance. This structural stability allows ammonium bicarbonate to retain more than 85% of its effective components even after accelerated aging.

[0058] Surface-grafted PVP long chains fix water molecules through hydrogen bonding, forming a dynamic hydration layer on the microcapsule surface. This hydration layer inhibits the migration and diffusion of the core material and avoids clumping caused by localized high humidity. In Comparative Example 3, due to the lack of PVP grafting, the ammonium citrate release rate increased to 15.4% during storage, triggering the pre-decomposition of ammonium bicarbonate and resulting in a 217% increase in free ammonia content.

[0059] The vacuum conditions of the three-stage mixing process effectively suppressed oxidation. Ultrasonic treatment resulted in a continuous, defect-free membrane structure in the coating layer, reducing the opportunity for oxygen to contact the active material. In Example 3, the pH value changed by only +0.18 under high temperature and humidity conditions, demonstrating that the process parameter design effectively maintained the chemical stability of the system. Comparative Example 5, which did not employ encapsulation treatment, experienced a pH shift of +1.12 after storage, leading to a 42% decrease in bulking efficiency.

[0060] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A food composite leavening agent, characterized by comprising: The composition comprises the following components in parts by mass: Ammonium bicarbonate: 25-30 parts; Microencapsulated ammonium citrate: 15-23 parts; Sodium pyrophosphate: 8-16 parts; L-potassium hydrogen tartrate: 5-9.5 parts; Trehalose: 13-17 parts; Surface-modified nanosilica: 0.5-1.3 parts; Hydroxypropylated cassava starch: 10-17 parts.

2. The food composite leavening agent according to claim 1, characterized in that, The microencapsulated ammonium citrate is formed by coating with β-cyclodextrin, and the thickness of the embedding layer is 16-20 μm.

3. The food composite leavening agent according to claim 2, characterized in that, The molar ratio of the β-cyclodextrin to ammonium citrate is 2.1-2.3:1, and the D50 particle size of the microcapsule particles is 30-34 μm.

4. The food composite leavening agent according to claim 1, characterized in that, The surface-modified nanosilica is a polyvinylpyrrolidone grafting modification product, with a grafting rate of 23%-27% and a particle size of 50-80 nm.

5. The food composite leavening agent according to claim 1, wherein The degree of substitution of the hydroxypropylated cassava starch is 0.08-0.12, and the water content is ≤8.5%.

6. A method for preparing a food composite leavening agent according to any one of claims 1 to 5, characterized in that, The method comprises the following steps: Step 1: preparing microencapsulated ammonium citrate; Step 2: preparing modified nanosilica; Step 3: mixing the modified nanosilica, the microencapsulated ammonium citrate and the remaining raw materials; Step 4: sieving.

7. The method for preparing a food compound leavening agent according to claim 1, characterized in that, The step 1 specifically comprises: First, prepare a 15-18 wt% aqueous solution of β-cyclodextrin, and heat to 58-62℃; Then add ammonium citrate crystals at a solid-liquid ratio of 1:3.8-4.2, and maintain the solution pH value at 6.8-7.2; Then add β-cyclodextrin in three portions with an interval of 9-11 min, and the total molar ratio between the β-cyclodextrin and ammonium citrate is 2.1-2.3:1; After mixing, perform spray drying, which specifically comprises: Inlet air temperature: 179-185℃, outlet air temperature: 76-80℃; Atomizing disc rotation speed: 19000-21000 rpm; Feeding rate: 8-12 mL / min.

8. The method of claim 6, wherein the food composite leavening agent is prepared by adding the leavening agent and the food additive to the food material and mixing them. The step 2 specifically comprises: The polyvinylpyrrolidone solution is an ethanol solution with a concentration of 7.5-8.5 wt%, and the ethanol purity is ≥99.7%; Put the nanosilica and the polyvinylpyrrolidone solution into a ball mill for grinding; the mass ratio of the nanosilica to the polyvinylpyrrolidone solution is 1:4.8-5.2, the ball milling medium is zirconium oxide ball with a diameter of 0.28-0.32 mm, and the ball-to-material ratio is 8:1-10:1; After ball milling, perform drying treatment, and the drying treatment conditions comprise: vacuum degree: -0.095 to -0.085 MPa, drying temperature: 48-52℃, and water content of the material after drying: ≤0.6%.

9. The method of claim 6, wherein the food composite leavening agent is prepared by adding the leavening agent and the food additive to the food material and mixing them. The step 3 specifically comprises: Primary mixing: mix ammonium bicarbonate and hydroxypropylated cassava starch at a rotation speed of 30-60 rpm for 7-11 min; Intermediate mixing: add microencapsulated ammonium citrate + sodium pyrophosphate + L-potassium hydrogen tartrate, and mix at a rotation speed of 13-17 rpm and a vacuum of -0.065 to -0.095 MPa for 10-20 min; Final mixing: after adding trehalose and surface-modified nanosilica, ultrasonic mixing is performed, and the ultrasonic frequency is 27-29 kHz, and the power density is 0.8-1.2 W / cm 3 , and the processing time is 4-9 min.

10. The method of claim 9, wherein the food composite leavening agent is prepared by adding the leavening agent and the food additive to the food material and mixing them. After the final mixing is completed, perform vibration sieving, the aperture of the sieve is 75-85 mesh, the amplitude is 2.3-3.2 mm, and the sieving time is 8-12 min.